Early childhood neuropedagogy: an opening window to the world - Varga, László (Rethinking childhood II: child and space, 2026)
An Early Childhood Neuropedagogy International Research Group & Lab (NeuPedLab ©) was established by Laszlo Varga, at the Benedek Elek Faculty of Pedagogy in Sopron, Hungary (Varga - Szécsi, 2018). The latest research emphasises childhood as a key factor. In recent years, research on young children’s early brain and emotional development has underscored its importance for later development. Integrating this “Brain-Based, Heart-Felt” research into classroom practice, however, requires a meaningful dialogue between educators and brain scientists that is to inform both research and ECE institutions. Linking brain and EQ research to ECE is extremely valuable to our understanding of child development and learning. This ongoing work promises to provide educational sciences with substantial new data, while also enriching and reshaping the training of nursery school and early childhood educators, as well as the innovation of early childhood education and research facilities (Szécsi – Varga – Mák, 2018). The human brain is a mysterious organ that poses serious learning challenges to scientists and child educators. Understanding how neuroscience can inform education strategies and finding out what teachers want and need to know about the ways children learn are two key drivers behind the neuro-education initiative. At birth, the brain is remarkably unfinished. The period up to approximately eight years of age represents the peak stage of brain development. From birth to about the age of eight the brain is a super-sponge—this is the brain’s most absorbent stage, where it actively learns from its environment. “Windows of opportunity” are sensitive periods in children’s lives when specific types of learning take place. Information flows easily into the brain through “windows” that are open for only a short duration. Then the “windows” close, and much of the fundamental architecture of the brain is completed and probably not going to change very much more. This raises a central question: What should we give, and what should we withhold, from children during these first crucial years? Children who have little opportunity to explore and experiment with their environment may fail to develop fully the neural connections and pathways that facilitate later learning. Further, exposure to trauma or chronic stress can make children more prone to emotional disturbances and less able to learn. Scientists are continually learning more about how young children’s brains develop. At the same time, teachers are looking for effective strategies to help children use their brains to their fullest capacity (Mák – Szécsi – Varga, 2018). This review also contributes to this dialogue by summarising what we already know about the learning process in the brain, and suggests how it might inform the teaching and learning process in the classroom. Intelligent investment in early childhood is key to fostering a happy life—a reminder of the immense opportunity and responsibility on our shoulders, since early years last forever.